GAPDH in neuroblastoma: Functions in metabolism and survival - Cornett, Kevin; Puderbaugh, Anna; Back, Olivia; Craven, Rolf (Frontiers in Oncology, 2022)
Neuroblastoma is a pediatric cancer of neural crest cells. It develops most frequently in nerve cells around the adrenal gland, although other locations are possible. Neuroblastomas rely on glycolysis as a source of energy and metabolites, and the enzymes that catalyze glycolysis are potential therapeutic targets for neuroblastoma. Furthermore, glycolysis provides a protective function against DNA damage, and there is evidence that glycolysis inhibitors may improve outcomes from other cancer treatments. This mini-review will focus on GAPDH (glyceraldehyde 3-phosphate dehydrogenase), one of the central enzymes in glycolysis. In addition to its role in metabolism, GAPDH has a surprisingly diverse number of localizations, including the nucleus, where it performs multiple functions, and the plasma membrane. One membrane-associated function of GAPDH is stimulating glucose uptake, consistent with a role for GAPDH in energy and metabolite production. The plasma membrane localization of GAPDH and its role in glucose uptake have been verified in neuroblastoma. Membrane-associated GAPDH also participates in iron uptake, although this has not been tested in neuroblastoma. Finally, GAPDH activates autophagy through a nuclear complex with Sirtuin. This review will discuss these activities and their potential role in cancer metabolism, treatment and drug resistance.